Identification and validation of autophagy-related genes in SSc - Liu Chen; Guo Xiaofang; Wei Maoyun; Xie Jiaxin; Zhang Xuting; Qi Qing; Zhu Ke (Open Medicine, 2024)
Multiple organs are affected by the complex autoimmune illness known as systemic sclerosis (SSc), which has a high fatality rate. Genes linked to autophagy have been linked to the aetiology of SSc. It is yet unknown, though, whether autophagy-related genes play a role in the aetiology of SSc. After using bioinformatics techniques to examine two databases (the GSE76885 and GSE95065 datasets) and autophagy-related genes, we were able to identify 12 autophagy-related differentially expressed genes that are linked to the pathophysiology of SSc. Additional examination of the receiver operating characteristic curve revealed that SFRP4 (AUC = 0.944, P < 0.001) and CD93 (AUC = 0.904, P < 0.001) might be utilized as trustworthy biomarkers for the diagnosis of SSc. The SSc group’s considerably greater CD93 and SFRP4 expression levels compared to the control group were further confirmed by qRT-PCR results. The autophagy-related genes SFRP4 and CD93 were found to be viable diagnostic indicators in this investigation. Our research sheds light on the processes by which genes linked to autophagy affect the pathophysiology of SSc.